2006
DOI: 10.1111/j.1600-0463.2006.apm_360.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, susceptibility profile and proteinase production of yeasts causing vulvovaginitis in Turkish women

Abstract: In this study the prevalence of vulvovaginal candidiasis (VVC), antifungal susceptibility and proteinase production of isolated Candida species were investigated. Vaginal swabs were collected from symptomatic women with vulvovaginitis attending the Obstetrics and Gynecology Clinic of Kocaeli University, Turkey. The relation between risk factors, such as pregnancy, diabetes mellitus, antibiotic and corticosteroid use, history of sexually transmitted diseases and contraceptive methods, was recorded. Candida spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
(52 reference statements)
1
11
2
3
Order By: Relevance
“…5 The rates of resistance observed in this study suggest the vaginal yeasts behave similarly to the yeasts causing systemic infections, 14,28 an observation that diverges from previous reports about VVC. 7,8,11 The susceptibility profiles of vaginal yeasts have been changing.…”
Section: Discussioncontrasting
confidence: 50%
“…5 The rates of resistance observed in this study suggest the vaginal yeasts behave similarly to the yeasts causing systemic infections, 14,28 an observation that diverges from previous reports about VVC. 7,8,11 The susceptibility profiles of vaginal yeasts have been changing.…”
Section: Discussioncontrasting
confidence: 50%
“…Despite the fact that C. albicans remains the main species of yeast isolated from vaginal specimens over the past few years, other non‐albicans species have also been isolated . Vaginal colonization of Candida species can be influenced by many factors, one of which is pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…) showed that Candida albicans is responsible for 70-90% of all vaginal candidiasis in Austria while many other studies showed that Candida glabrata has been the most frequent pathogen that causes vaginal Candidiasis (Novikova et al, 2002;Lopes Consolaro et al, 2004). Ozcan et al (2006) reported that C. glabrata is responsible for 14% of infections in immune competent women. Candida is a member of normal flora in vagina and oral cavity; however, there are many predisposing factors that can lead to these infections such as pregnancy, long term use of antibiotics, diabetes mellitus, using of corticosteroids, HIV infection, and being immunocompromised (Fidel and Sobel, 1996;Duerr et al, 1997Duerr et al, , 2003Corsello et al, 2003;Beltramene et al, 2006).…”
Section: Introductionmentioning
confidence: 99%